Control Shift - Theodora Chatzi Rodopoulou (A+BE: Architecture and the Built Environment)
The legacy of industrialisation counts only a few decades of being accepted as cultural heritage. The change of perceptions over its connotation and significance, from a menace to historic landscapes to an outstanding historical resource, took place in an era of massive sociocultural and economic upheavals. Those far-reaching developments reshaped both the theory and the practice of heritage conservation.